Black Sheep or Scapegoats? Implementable Monitoring Policies under Unobservable Levels of Misbehavior - Berno Buechel; Gerd Mühlheusser (Center for Economic Studies and ifo Institute (CESifo), 2014)
An authority delegates a monitoring task to an agent. It can only observe the number of detected offenders, but neither the monitoring intensity chosen by the agent nor the resulting level of misbehavior. We provide a necessary and sufficient condition for the implementability of monitoring policies. Typically, several monitoring intensities give rise to the same number of detected offenses, and only the minimum of these can be implemented. In equilibrium, a large fraction of potential offenders cannot be deterred.
Keywords: K42; D73; 330; monitoring; deterrence; unobservable misbehavior; victimless crime; doping; law & economics